After the Fall: Folkloristics in Ukraine After 1991 - Klymasz, Robert (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1999)
Works published during the first years of independence show that post-Soviet folkloristics in Ukraine were in a state of flux. In spite of the eclipse of state funding and the concomitant initial period of disorientation, this period is also characterized by a number of important innovations that were especially significant for the advancement of Ukrainian folklore scholarship. However, some areas of investigation (such as folk religion) remain understudied.